"Gekontroleerde" eksegese en/of "kreatiewe" uitleg - Deist, Ferdinand (Hervormde teologiese studies, 1988)
'Controlled' exegesis and/or 'creative' interpretation Exegetes often regard epistemological questions as unnecessary and of 'academic' interest. Yet, answers to questions such as; 'What is a text?' and 'What is meaning?' are of fundamental importance in the argument about exegetical method(s). For instance, exegetical techniques focussing on the 'structure' of texts, although often claimed to be anti-positivist, do not of themselves imply a divorce from positivism, because the epistemological frameworks within which exegetical techniques are applied, determine their hermeneutical function. The influence of epistemological choices on the definition of the entities 'text' and 'meaning' as well as on the evaluation of textual expositions is discussed, and a few remarks are made on the (often determining) influence of theological tradition on such epistemological choices.